EPIDEMIC PAROTITIS IN CHILDREN - THE URGENCY OF THE PROBLEM - G. A. Harchenko; O. G. Kimirilova (LLC "Diagnostics and Vaccines", 2017)
The aim of the study was to determine the clinical and epidemiological features of Epidemic parotitis in children in the Astrakhan Region under conditions of vaccine prophylaxis. 260 cases of laboratory-confirmed Epidemic parotitis in children under 17 years of age have been analyzed.Contact with diseased Epidemic parotitis was found in 180 (69,2%) of affected children. In the age structure of the patients, children aged 3 to 9 years (73,8%) prevailed, of which 87,5% of children in this age group had vaccination and revaccination against Epidemic parotitis. Patients aged 9 to 17 years accounted for 26,2% of cases with an immune stratum of 76,5%. Severe forms of the disease were noted when a combination of Epidemic parotitis with orchitis, pancreatitis, meningitis. The epidemiological process of Epidemic parotitis infection in children, under conditions of vaccine prevention, is characterized by an increase in the number of patients among older children and adolescents up to 26,2%. The decrease in the immune stratum, among infected children, compared with the recommended level of coverage with vaccination and revaccination against Epidemic parotitis 95% of children, may be the cause of the increase in the incidence of this pathology in the region. In the structure of clinical forms, medium-severe forms of the disease predominate (63,9%). Displacement of morbidity by Epidemic parotitis in the direction of older and adolescent years may indicate a decrease in the intensity of postvaccinal immunity after revaccination at the age of 6 years, which calls for discussion of the need for a second planned revaccination against Epidemic parotitis at the age of 15-17.